Bibliotherapy in the Elementary Classroom: Using Literature to Navigate Trauma - Carpenter, Shelby B. (My University, 2019)
The positive impacts of reading come together in a litany of benefits one cannot ignore: reduce stress levels, improve analytical thinking, enhance memory, expands intelligence, bolster vocabulary, strengthen writing skills, and many more. But what about the advantages on an individual’s overall mental wellness that may come from reading? Officially defined by the American Library Association in 1966, bibliotherapy is the use of books in the purpose of healing, flowing in the vein of creative arts therapy. Bibliotherapy uses an individual's relationship or connection to the content of a book to help address trauma, hardships, or mental disorders. Using books in bibliotherapy can open up a Children are not immune to traumatic life events. From divorce to loss of a loved one, young individuals may have difficulty navigating the breadth of emotions saddled with such negative instances. Bibliotherapy is yet another benefit of reading that may set students up for success academically, socially, emotionally, and developmentally. This literary review outlines the history of bibliotherapy, scholarly articles delineating the implementation of bibliotherapy at an elementary level, as well as my conclusive thoughts on using literature to comprehend life events and their inevitable impact. By exploring these academic avenues, I hope to be able to create a better sense of understanding how I may use bibliotherapy in my own classroom to teach and help students who have experienced hardships in their young lives, applying this information beyond my written work and in my professional career as an elementary educator.